The impact of Stellenbosch Square on retail buying patterns in Paradyskloof - Van der Merwe, J. M. P. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2006.